Legal Protection for Workers Experiencing Depression Due to Workplace Bullying: Reconstructing Corporate Responsibility in Indonesian Labor Law - Manda Berinandus; Rineke Sara (Jurnal Sosial Teknologi, 2026)
Workplace bullying has emerged as a significant issue affecting workers' mental health and well-being. In many cases, repeated psychological intimidation, humiliation, or exclusion in the workplace can have serious mental health consequences, including depression. Despite growing awareness of mental health protection in employment relationships, Indonesian labor law does not explicitly regulate workplace bullying or corporate liability for psychological harm experienced by workers. This normative legal research aims to analyze the existing legal protection framework for workers experiencing depression due to workplace bullying and to reconstruct the concept of corporate liability in Indonesian labor law. This research uses legislative, conceptual, and comparative approaches by examining relevant laws and regulations, legal doctrine, and international standards related to mental health protection in the workplace. The research findings show that Indonesian labor regulations still focus on physical aspects of occupational safety and health, leaving significant regulatory gaps regarding psychological safety in the workplace. Consequently, workers experiencing depression due to workplace bullying often face difficulties in obtaining effective legal remedies. This study proposes a reconstruction of corporate responsibility through the integration of psychological safety aspects into occupational health protection, the application of the corporate duty of care principle, and the establishment of preventative mechanisms within corporate governance. This reconstruction is expected to strengthen legal protection for workers' mental health while encouraging the creation of more humane and equitable industrial relations.